STATIC STRAINING AND LONGITUDINAL OSCILLATIONS OF UNDERGROUND PIPELINE BUILT ON BLOCK FOUNDATION - Struk, A. B.; Vaskovskyi, M. I.; Shatskyi, I. P.; Makoviichuk, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The article considers the issues of forecasting the strength of underground pipelines, which are operated on seismically active sections of the route, composed of relatively rigid mobile blocks. According to the literature, the problems of the influence of the interaction of base faults on the stress state of the pipeline have not been studied to date. The aim of the work is to develop a model for the analysis of abnormal stresses in the underground pipeline on a damaged basis caused by static or time-harmonious mutual movement of its blocks along the axis of the pipe in the presence of several faults. Boundary value problems for differential equations of static tensile-compression and steady-state longitudinal oscillations of a tubular rod with discontinuous right-hand sides are formulated. Based on the analytical solutions of these problems for the cases of antisymmetric and symmetric displacement of the foundation blocks, the distributions of axial displacement and equivalent stress in the pipe, depending on the distance between faults and the frequency of forced oscillations, are investigated.